Psychological motivational aspects of distance learning - Бурлачук, Леонид; Абдимуса , Жулдыз (Pedagogy and Psychology, 2022)
This article presents the results of a study of purposeful interaction between a student and a teacher in online learning. The aim of the study was to study the psychological motivational aspects of distance learning. In the course of the survey and survey aimed at studying the influence of distance learning on the level of academic performance and emotional intelligence, as well as a psychodiagnostics study of the motivational-value sphere using a bank of tests, which included the following methods: modifications by A. Rean; Kazantseva’s methodology for studying attitudes to academic subjects, adapted for university students; Orientation questionnaire B. Bass to determine personal orientation; Morphological test of life values ​​by V. F. Sopova, L. V. Karpushina; Willpower test; Achievement motivation assessment scale; Questionnaire to assess the need for success; Approval Motivation Scale. As a result of the research, it was revealed that without direct contact and the implementation of real practical tasks in the process of distance learning, junior students lose interest in the subject being studied, they do not see the possibility of applying the acquired knowledge in their subsequent professional activities. The conclusion is made about the uncertainty of life values ​​among undergraduate students, which reflects their psychological personal immaturity, and the presence of intrapersonal contradictions may be associated with a dependent position and the struggle of motives. Therefore, the educational process should be aimed not only at acquiring knowledge, but also include an educational component, the formation of the personality of a future specialist, without which it is impossible to develop such key competencies as critical thinking and creativity.